Research, Intuition, and Politics in Accounting Inquiry. - Gerboth, Dale L. (The Accounting Review, 1973)
This article presents information on the accounting research program and how accounting inquiry must be directed toward understanding human purposes. Accounting research has a variety of powerful techniques for systematic analysis. Statistics, economics, operations research, behavioral science, and other disciplines have furnished tools that excel in rigorous investigation. Those tools can force implicit concepts into explicit form and establish the circumstances in which the concepts are valid. They can test the internal consistency of a variety of propositions. They can systematically explore the range of possible outcomes resulting from specified acts. In short, the techniques of accounting research excel when analysis is to be rigorous, logical, and systematic. The choice, however, between intuition and research in accounting inquiry is false they are complementary rather than competing. Decisions in accounting, as in other human endeavor, depend primarily on the inarticulate background knowledge of seasoned men, and it does not follow that research has no role. To the contrary, explicit information that has been subjected to systematic analysis should be carefully considered by a decision maker lucky enough to have it available.